PDTC Alleviates Depressive Symptoms and Colon Tissue Injury via Inhibiting NO Overproduction in CUMS Rats - Yang, Lejin; Chen, Hui; Wang, Dongdong; Nie, Shuping; Du, Jinge; Lu, Ming (Frontiers in Neuroscience, 2019)
Background: The accumulated evidence demonstrates that stress plays an important role in the pathogenesis of depression association with intestinal dysfunctions. However, the mechanisms remain unresolved. Methods: 40 male Wistar rats were employed and randomly divided into four groups in equal: control, PDTC+CUMS, FLX+CUMS, CUMS. Western blotting and qRT-PCR were used to examine the levels of nitric oxide (NO), Nuclear factor kappa beta(NF-κB), inducible nitric oxide synthase (iNOS) and iNOS mRNA in spinal cord L1-2 and colon. Key Results: Chronic and unpredictable mild stress (CUMS) increased serum CORT level, decreased body weight, sucrose preference and altered OFT performance, while increased levels of NO, iNOS mRNA, iNOS and NF-κB protein in colon and spinal cord were accompanied with histopathological changes in colon. Pretreatment with a NF-κB inhibitor pyrrolidine dithiocarbamate (PDTC) reversed these parameters. Fluoxetine failed in prevention of NO increase in both spinal cord and colon, while iNOS protein level, although not statistically significantly increased compared to control, was not decreased compared to CUMS. Also, Fluoxetine failed to prevent histological changes. Conclusions: In conclusion, the NF-κB/iNOS pathway might be involved in the mechanism of CUMS-induced depressive like behavior and colon tissue injury.